(untitled) (Revista Nacional de Odontología, 2014)
Fusion is defined as the partial or complete union of two or more teeth during their development; it can occur between normal teeth or between a normal tooth and a supernumerary tooth. This anomaly can be unilateral or bilateral and can affect any teeth, although deciduous teeth are more frequently damaged. It can also affect the patient’s appearance, cause changes in the dental arch space, lead to cavities and affect periodontal structures. This article presents the case of 13-year-old who came in for consultations due to repeated inflammatory events at the level of gum 22. These episodes stem from the fusion of tooth 22 with a supernumerary. After radiographic evaluation and adequate planning, the supernumerary tooth was extracted, and the palatal groove formed by the fusion of both teeth was eliminated, which had been the main cause of the patient’s periodontal-endodontic lesion.